Composite positive plate as well as preparation method and application thereof

By coating the positive electrode sheet in situ after the homogenization coating process, the side reaction problem of high-voltage positive electrode materials in the electrolyte is solved, the electronic conductivity and high voltage resistance are improved, and lithium ions are improved Fast charging and power performance of secondary batteries.

CN119153629APending Publication Date: 2024-12-17SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411544517.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing high-voltage positive electrode materials have side reactions such as electrolyte decomposition in the electrolyte, which leads to the rapid attenuation of the capacity of lithium-ion secondary batteries, limiting its large-scale application in the product, and at the same time, the surface coating treatment reduces the electronic conductivity. Impacts power performance and fast charging performance.

Method used

After the homogenization coating process of the positive electrode sheet, the unpressed positive electrode sheet is immersed in a fluid containing a coating additive with lithium ion conductivity and electronic insulation, and a in-situ cladding layer is formed and penetrated into the positive electrode sheet. Internal to improve high voltage resistance and electronic conductivity.

Benefits of technology

It effectively blocks the direct contact between the high-voltage positive electrode material and the electrolyte, reduces oxidation and decomposition, improves the electronic conductivity of the positive electrode material, and takes into account the high-voltage resistance and power performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153629A_ABST
    Figure CN119153629A_ABST
Patent Text Reader

Abstract

The invention provides a composite positive plate as well as a preparation method and application thereof. The method comprises the following steps that an unpressed positive plate is soaked in fluid containing a coating additive, a precursor material is obtained after drying, and the positive plate does not contain the coating additive; and pressing the precursor material to obtain the composite positive plate. According to the invention, after the homogenate coating process of the positive electrode slurry is completed and a pole piece electronic conductive network is preliminarily constructed, in-situ coating is carried out on the surface of the positive electrode active material exposed in the positive electrode piece, so that the high voltage resistance and the electronic conductivity of the positive electrode material are comprehensively improved; therefore, the fast charging performance and the power performance of the secondary battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cathode material technology, specifically relating to a composite cathode sheet, its preparation method, and its application. Background Technology

[0002] Lithium-ion rechargeable batteries offer advantages such as high energy density, long cycle life, and environmental friendliness. In recent years, user anxiety regarding the range of electric vehicles has created an urgent need for lithium-ion power batteries that balance high energy density with good fast-charging performance. High-voltage nickel-cobalt-manganese (NCM) lithium oxide and lithium-rich manganese-based materials have attracted significant attention due to their high energy density. Furthermore, spinel-structured NCM materials offer advantages such as low material cost, good thermal stability, excellent kinetics, high voltage plateau, and high energy density. However, these cathode materials are susceptible to side reactions such as electrolyte decomposition at higher potentials, leading to rapid capacity decay and limiting their large-scale application in products.

[0003] To address these issues, researchers often perform surface coating treatments on high-voltage cathode materials. This treatment effectively isolates the electron conduction between the cathode material and the electrolyte, ultimately reducing side reactions and improving battery cycle stability and safety. However, while these surface coatings reduce interfacial side reactions between the cathode material and the electrolyte, they also decrease the electron conductivity of the cathode material surface, thus affecting the battery's power performance and fast-charging performance. In this situation, even with the addition of a large amount of conductive agent during cathode preparation, the formation of an electronic insulating layer on the cathode material surface still fails to significantly improve the electronic conductivity of the cathode.

[0004] Therefore, there is an urgent need in this field to develop a cathode that can maintain the stability of high-voltage cathode materials while comprehensively improving the power performance and fast-charging performance of secondary batteries. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a composite positive electrode sheet, its preparation method, and its application. The present invention, after the positive electrode slurry has undergone a homogenization and coating process and a preliminary electronic conductive network has been constructed, further involves in-situ coating of the exposed positive electrode active material surface within the positive electrode sheet. This comprehensively improves the high-voltage resistance and electronic conductivity of the positive electrode material, thereby enhancing the fast-charging performance and power performance of the secondary battery.

[0006] To achieve this objective, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing a composite positive electrode sheet, the method comprising the following steps:

[0008] An unpressed positive electrode sheet is immersed in a fluid containing a coating additive and dried to obtain a precursor material, wherein the positive electrode sheet does not contain the coating additive; the precursor material is pressed to obtain the composite positive electrode sheet.

[0009] This invention enables in-situ coating of the positive electrode active material while ensuring good electronic conductivity of the positive electrode sheet. Specifically, after the normal homogenization, coating, and drying process of the positive electrode sheet, a step is added whereby the unpressed positive electrode sheet is immersed in a fluid containing a coating additive that provides both lithium-ion conductivity and electronic insulation. This allows the coating additive material to penetrate deep into the positive electrode sheet, rather than being limited to its surface. Simultaneously, since the active material within the positive electrode sheet is coated after a wet coating process, and an electronic conductive network has already been initially constructed within the positive electrode sheet during coating, resulting in good electronic conductivity, a protective layer is ultimately formed on the surface of the positive electrode active material with good electronic conductivity. This layer prevents direct contact between the high-voltage positive electrode material and the electrolyte, and reduces the oxidative decomposition of the electrolyte on the positive electrode surface. Compared to traditional techniques that involve coating the cathode material during its preparation, the method provided by this invention avoids covering the electron transport sites on the surface of the cathode active material with the coating layer, thereby further improving the electronic conductivity of the cathode material and ultimately achieving a balance between the high voltage resistance and power performance of the secondary battery.

[0010] Preferably, the material of the positive electrode sheet includes a positive electrode active material, a conductive agent, and a binder in a mass ratio of (92-97):(1-3):(2-5), such as 92:3:5, 93:2:5, 94:3:3, 95:3:2, 96:2:2, 97:1:2, etc.

[0011] Preferably, the charging voltage platform of the positive electrode active material is not lower than 4.4V, for example, it can be 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V, 4.8V, etc.

[0012] In this invention, the positive electrode active material includes, for example, at least one of spinel phase lithium nickel manganese oxide (LNMO), lithium-rich manganese-based material (LMR), lithium nickel cobalt manganese oxide, or lithium cobalt oxide.

[0013] Preferably, the conductive agent is interspersed between the positive electrode active materials to form an electronic conductive network.

[0014] Preferably, the conductive agent is a one-dimensional conductive agent material, thereby ensuring that the positive electrode has good electronic conductivity.

[0015] Preferably, the one-dimensional conductive agent material includes at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, or vapor-grown carbon fiber reinforcement (VGCF).

[0016] Preferably, based on the total mass of the positive electrode material as 100%, the mass percentage of the one-dimensional conductive agent material is 0.1 wt.%-2 wt.%, for example, it can be 0.1 wt.%, 0.15 wt.%, 0.2 wt.%, 0.25 wt.%, 0.5 wt.%, 0.8 wt.%, 1 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, etc. This invention, by controlling the mass percentage of the one-dimensional conductive agent material, achieves optimal electronic connections between the positive electrode active material and the current collector within the positive electrode sheet. If a low content of one-dimensional conductive agent is used, the ohmic resistance between the active material on the surface of the positive electrode and the current collector will be too high; if a high content of one-dimensional conductive agent is used, the conductive agent is prone to agglomeration and is not easy to disperse. Too much one-dimensional conductive agent will not bring a proportional improvement in conductivity.

[0017] In this invention, when the one-dimensional conductive agent material is a single-walled carbon nanotube, the mass percentage of the single-walled carbon nanotube is 0.1 wt.% to 0.3 wt.%, based on the total mass of the positive electrode material as 100%. For example, it can be 0.1 wt.%, 0.12 wt.%, 0.15 wt.%, 0.18 wt.%, 0.2 wt.%, 0.22 wt.%, 0.25 wt.%, 0.28 wt.%, 0.3 wt.%, etc.

[0018] In this invention, when the one-dimensional conductive agent material is multi-walled carbon nanotubes and / or vapor-grown carbon fiber reinforcement, the mass percentage of the one-dimensional conductive agent material is 0.5 wt.%-2 wt.%, based on the total mass of the positive electrode material as 100%, for example, it can be 0.5 wt.%, 0.8 wt.%, 1 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, etc.

[0019] In this invention, the conductive agent also includes carbon black and / or graphene, which can be used in combination according to actual conditions by those skilled in the art.

[0020] In this invention, the adhesive exemplarily includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, or polyacrylonitrile.

[0021] Preferably, the porosity of the positive electrode sheet is 45%-55%, for example, it can be 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, etc. This invention, by controlling the porosity of the positive electrode sheet, ensures that the positive electrode sheet can be fully wetted. Using a positive electrode sheet with low porosity would be detrimental to the coating process; using a positive electrode sheet with high porosity would result in insufficient contact between the positive electrode active material particles and the conductive agent, thereby affecting the subsequent electronic conductivity of the positive electrode sheet.

[0022] Preferably, the impregnation process includes vacuum pressure impregnation using a vacuum pressure impregnation device, which helps the coating additive to fully penetrate into the pores of the positive electrode sheet.

[0023] Preferably, the vacuum pressure impregnation device includes an impregnation unit, a vacuum unit, and a pressurization unit.

[0024] In this invention, the vacuum pressure impregnation device further includes a dehydration unit to maintain the dryness of the device's interior.

[0025] Preferably, the upper part of the impregnation unit is connected to the vacuum unit through a first connecting valve.

[0026] Preferably, the vacuum unit includes a vacuum tank and a vacuum pump. The vacuum tank is connected to the impregnation unit through a first connecting valve. The vacuum unit is used to extract gas from the impregnation unit to form a vacuum.

[0027] Preferably, the upper part of the impregnation unit is connected to the pressurization unit via a second connecting valve.

[0028] Preferably, the pressurizing unit includes a pressure tank and a pressure pump. The pressure tank is connected to the impregnation unit via a second connecting valve. The pressurizing unit is used to generate pressure to impregnate the coating additive into the unpressed positive electrode sheet of the impregnation unit.

[0029] In this invention, the first connecting valve and the second connecting valve exemplarily include solenoid valves.

[0030] Preferably, the impregnation unit includes an impregnation tank, an infrared drying oven, and a conveying unit. The conveying unit conveys the unpressed positive electrode sheet to the impregnation tank for impregnation treatment, and after the impregnation is completed, it is conveyed to the infrared drying oven for drying to obtain the precursor material.

[0031] In this invention, by alternately opening and closing the first connecting valve or the second connecting valve, the impregnation unit is in a state similar to "breathing" at a certain frequency of "vacuuming-positive pressure".

[0032] Preferably, the time for each vacuum pressure impregnation treatment is 1-20s, more preferably 2-5s, for example, it can be 1s, 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s, 11s, 12s, 13s, 14s, 15s, 16s, 17s, 18s, 19s, 20s, etc.

[0033] Preferably, the maximum pressure difference during each vacuum pressure impregnation process is 20-60 kPa, more preferably 30-50 kPa, and can be, for example, 20 kPa, 22 kPa, 25 kPa, 28 kPa, 30 kPa, 32 kPa, 35 kPa, 38 kPa, 40 kPa, 42 kPa, 45 kPa, 48 kPa, 50 kPa, 52 kPa, 55 kPa, 58 kPa, 60 kPa, etc.

[0034] This invention optimizes the impregnation effect by controlling the time and pressure peak-to-valley difference during the vacuum pressure impregnation process, ensuring that the electrode remains in the impregnation tank for a time greater than or equal to one or more vacuum pressure impregnation cycles, and avoiding liquid splashing in the impregnation tank due to excessive pressure difference or impregnation effect due to excessively low pressure difference.

[0035] Preferably, the time interval between two consecutive vacuum pressure impregnation treatments is 1-20s, more preferably 2-5s, for example, it can be 1s, 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s, 11s, 12s, 13s, 14s, 15s, 16s, 17s, 18s, 19s, 20s, etc.

[0036] This invention adjusts the frequency of vacuum pressure impregnation treatment so that a fixed position of the electrode is immersed in the impregnation liquid for a period of time greater than one or more vacuum pressure impregnation treatment cycles, which is beneficial for thorough impregnation.

[0037] Preferably, the coating additive includes a lithium-ion conductor.

[0038] Preferably, the lithium-ion conductor comprises any one or a combination of at least two of lithium borate, lithium silicate, lithium aluminate, lithium phosphate, polycyanoacrylate, or inorganic solid electrolyte.

[0039] Preferably, based on the total mass of the positive electrode active material (100%), the mass percentage content of the coating additive is 0.5 wt.%-5 wt.%, more preferably 0.5 wt.%-3 wt.%, for example, it can be 0.5 wt.%, 0.8 wt.%, 1 wt.%, 1.2 wt.%, 1.5 wt.%, 1.8 wt.%, 2 wt.%, 2.2 wt.%, 2.5 wt.%, 2.8 wt.%, 3 wt.%, 3.2 wt.%, 3.5 wt.%, 3.8 wt.%, 4 wt.%, 4.2 wt.%, 4.5 wt.%, 4.8 wt.%, 5 wt.%, etc. This invention optimizes the coating effect, energy density, and fast-charging performance of the positive electrode sheet by controlling the mass percentage content of the coating additive. If a low content of coating additives is used, the positive electrode active material will not be adequately coated, and the electrolyte will easily oxidize and decompose on its surface, thus affecting the battery's high voltage resistance and cycle performance. If a high content of coating additives is used, the battery's energy density will be reduced and the lithium-ion transport resistance will be increased, resulting in a decrease in the battery's fast charging performance.

[0040] Preferably, when the coating additive is lithium borate, the mass percentage of lithium borate is 0.5 wt.% to 2 wt.%, based on the total mass of the positive electrode active material as 100%, for example, it can be 0.5 wt.%, 0.8 wt.%, 1 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, 1.5 wt.%, 1.6 wt.%, 1.7 wt.%, 1.8 wt.%, 1.9 wt.%, 2 wt.%, etc.

[0041] Preferably, when the coating additive is an inorganic solid electrolyte, the average particle size of the inorganic solid electrolyte is ≤200nm. The average particle size of the inorganic solid electrolyte can be, for example, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 120nm, 150nm, 180nm, 200nm, etc. If the average particle size is too large, it is not easy to form a uniform and dense coating layer on the surface of the positive electrode active material. Furthermore, the ratio of the average particle size of the inorganic solid electrolyte to the average particle size of the positive electrode active material is ≤1 / 20, preferably 1 / 30-1 / 20, for example, 1 / 20, 1 / 23, 1 / 25, 1 / 22, 1 / 28, 1 / 25.3, 1 / 30, etc.

[0042] This invention adjusts the ratio of the average particle size of the inorganic solid electrolyte to the average particle size of the positive electrode active material, making it easier for the inorganic solid electrolyte particles to disperse and uniformly coat the surface of the positive electrode material. If an inorganic solid electrolyte with a larger average particle size is used, it is difficult for fluids containing coating additives to penetrate deep into the interior of the positive electrode sheet through the pores.

[0043] Preferably, when the coating additive is an inorganic solid electrolyte, the fluid containing the coating additive also includes a dispersant.

[0044] Preferably, based on the total mass of the positive electrode active material as 100%, the mass percentage of the dispersant is not higher than 1 wt.%, for example, it can be 0.1 wt.%, 0.2 wt.%, 0.5 wt.%, 0.8 wt.%, 1 wt.%, etc.

[0045] In this invention, the dispersant exemplary includes at least one of polyvinylidene fluoride, lithium polyacrylate, polyacrylic acid, polyacrylonitrile, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, potassium carboxymethyl cellulose, or polypropylene carbonate.

[0046] Preferably, the solvent in the fluid containing the coating additive includes at least one of deionized water, ethanol, acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, or N,N-dimethylacetamide.

[0047] In this invention, the fluid containing the coating additive is exemplarily in the form of a solution, colloid, or slurry.

[0048] In this invention, when the coating additive is lithium borate, deionized water is used as the solvent. After impregnation, the positive electrode sheet is transferred to an 80°C oven for drying to remove free water, and then transferred to a vacuum oven for further drying at a temperature of 240°C-280°C (e.g., 240°C, 250°C, 260°C, 270°C, 280°C, etc.) to remove bound water. The drying temperature is preferably 250°C, and the binder used in the positive electrode sheet is preferably polytetrafluoroethylene.

[0049] In this invention, when the coating additive is lithium aluminate, it is impregnated with an aqueous solution of lithium tetrahydroxyaluminate. After impregnation, the positive electrode sheet is transferred to an 80°C oven for drying to remove free water, and then transferred to a 120°C vacuum oven for further drying.

[0050] Preferably, the concentration of the solute in the fluid containing the coating additive is 1 wt.%-15 wt.%, more preferably 2 wt.%-8 wt.%, for example, it can be 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.%, 15 wt.%, etc.

[0051] Preferably, the viscosity of the fluid containing the coating additive is no higher than 1000 cP, more preferably no higher than 500 cP, and can be, for example, 100 cP, 150 cP, 200 cP, 250 cP, 300 cP, 350 cP, 400 cP, 450 cP, 500 cP, 550 cP, 600 cP, 650 cP, 700 cP, 750 cP, 800 cP, 850 cP, 900 cP, 950 cP, 1000 cP, etc. This invention, by controlling the viscosity of the fluid containing the coating additive, allows the coating agent to smoothly impregnate the interior of the positive electrode sheet. If a fluid containing the coating additive with a high viscosity is used, the coating agent may not be able to fully penetrate to the bottom of the positive electrode sheet.

[0052] In a second aspect, the present invention provides a composite positive electrode sheet, which is prepared by the method for preparing a composite positive electrode sheet according to the first aspect.

[0053] Thirdly, the present invention provides a secondary battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the positive electrode comprises a composite positive electrode as described in the second aspect.

[0054] The secondary battery assembled from the composite positive electrode provided by this invention can comprehensively improve the power performance, high voltage resistance, and fast charging performance of the secondary battery.

[0055] Preferably, the negative electrode active material in the negative electrode sheet includes at least one of graphite, soft carbon, hard carbon, silicon oxide, silicon carbon, or lithium titanate.

[0056] Preferably, the electrolyte comprises a metal salt, an additive, and a solvent.

[0057] Preferably, the metal salt includes a lithium salt.

[0058] Preferably, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, or lithium bis(trifluoromethyl)sulfonylimide.

[0059] Preferably, the additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, propylene sulfate, 1,3-propanesulfonate lactone, 1,4-butanesulfonate lactone, dimethyl methane disulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium difluorooxalate phosphate, or lithium dioxalate borate.

[0060] Preferably, the solvent comprises any two or at least three of the following: ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethyl acetate, propyl propionate, ethyl propionate, methyl propionate, fluoroethylene carbonate, or ethyl fluorocarbonate.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] This invention provides a method for preparing composite cathode sheets. This method enables in-situ coating of the active cathode material while ensuring good electronic conductivity. Specifically, after the normal homogenization, coating, and drying process, an additional step is added where the unpressed cathode sheet is immersed in a fluid containing a coating additive that provides both lithium-ion conductivity and electronic insulation. This allows the coating additive to penetrate deep into the cathode sheet, rather than being confined to its surface. Simultaneously, since the active material within the cathode sheet is coated after a wet coating process, and an electronic conductive network has already been preliminarily constructed within the cathode sheet during coating, the cathode sheet exhibits good electronic conductivity. Ultimately, a protective layer is formed on the surface of the electronically conductive active cathode material, thereby preventing direct contact between the high-voltage cathode material and the electrolyte and reducing oxidative decomposition of the electrolyte on the cathode surface. Compared to traditional techniques that involve coating the cathode material during its preparation, the method provided by this invention avoids covering the electron transport sites on the surface of the cathode active material with the coating layer, thereby further improving the electronic conductivity of the cathode material and ultimately achieving a balance between the high voltage resistance and power performance of the secondary battery. Attached Figure Description

[0063] Figure 1 This is a schematic diagram illustrating the fabrication principle of the composite positive electrode in this invention.

[0064] Figure 2 This is a schematic diagram of the vacuum pressure impregnation device in this invention. Detailed Implementation

[0065] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be considered as specific limitations thereof.

[0066] When spinel-phase lithium nickel manganese oxide with a charging voltage platform of 5V is selected as the positive electrode active material, the preparation method of the unpressed positive electrode sheet provided in the embodiments and comparative examples of this invention includes the following steps: spinel-phase lithium nickel manganese oxide, multi-walled carbon nanotubes, conductive carbon black, and polytetrafluoroethylene are mixed in a mass ratio of 95:1:2:2, homogenized to prepare a positive electrode slurry, and the positive electrode slurry is coated onto both sides of an aluminum foil current collector. After drying, a positive electrode sheet is obtained, wherein the areal density of the single-sided coating of the positive electrode sheet is 22.30 mg / cm². 2 The porosity is 48%.

[0067] When lithium-rich manganese-based materials are selected as the positive electrode active material, the preparation method of the unpressed positive electrode sheet provided in the embodiments and comparative examples of this invention includes the following steps: lithium-rich manganese-based materials, multi-walled carbon nanotubes, conductive carbon black, and polytetrafluoroethylene are mixed in a mass ratio of 95:1:2:2, homogenized to prepare a positive electrode slurry, and the positive electrode slurry is coated onto both sides of an aluminum foil current collector. After drying, a positive electrode sheet is obtained, wherein the areal density of the coating on one side of the positive electrode sheet is 12.1 mg / cm². 2 The porosity is 47.8%.

[0068] Example 1

[0069] This embodiment provides a method for preparing a composite positive electrode sheet, the preparation principle of which is as follows: Figure 1 As shown, the method includes the following steps:

[0070] Unpressed spinel-phase lithium nickel manganese oxide cathode sheets were thoroughly wetted in a 4 wt.% lithium borate aqueous solution (viscosity 7.4 cP). The total mass of spinel-phase lithium nickel manganese oxide was 100%, and the mass percentage of lithium borate was 0.8 wt.%. Each vacuum pressure impregnation treatment lasted 2 seconds, with a maximum pressure difference of 30 kPa during each treatment. The interval between two adjacent vacuum pressure impregnation treatments was 2 seconds. Afterward, the cathode sheets were removed and placed in a 60℃ infrared forced-air oven for pre-drying for 5 minutes. Once pre-dried, the cathode sheets were transferred to a vacuum oven and dehydrated at 250℃ for 2 hours. After cooling to room temperature, the precursor material was obtained.

[0071] Among them, such as Figure 2 As shown, the vacuum pressure impregnation apparatus used in this embodiment includes an impregnation unit, a vacuum unit, a pressurization unit, and a dehydration unit. The upper part of the impregnation unit is connected to the vacuum unit via a first solenoid valve. The vacuum unit includes a vacuum tank and a vacuum pump. The vacuum tank is connected to the impregnation unit via the first solenoid valve, and the vacuum unit is used to extract gas from the impregnation unit to create a vacuum. The upper part of the impregnation unit is connected to the pressurization unit via a second solenoid valve. The pressurization unit includes a pressure tank and a pressure pump. The pressure tank is connected to the impregnation unit via the second solenoid valve, and the pressurization unit is used to generate pressure to impregnate lithium borate into the unpressed positive electrode sheet in the impregnation unit. The impregnation unit includes an impregnation tank, an infrared drying chamber, and a conveyor unit. The conveyor unit includes a motor, an unwinding roller, a winding roller, and a conveyor belt disposed between the unwinding roller and the winding roller. The conveyor unit conveys the unpressed positive electrode sheet to the impregnation tank for impregnation treatment, and after completion, it is conveyed to the infrared drying chamber for drying to obtain the precursor material.

[0072] The precursor material was rolled and slit in an environment with a dew point of -40°C to obtain the composite positive electrode sheet with a size of 30mm×50mm.

[0073] Example 2

[0074] This embodiment provides a method for preparing a composite positive electrode sheet, the method comprising the following steps:

[0075] Unpressed spinel-phase lithium nickel manganese oxide cathode sheets were thoroughly wetted in a 3 wt.% lithium silicate aqueous solution (viscosity 5.8 cP). The total mass of spinel-phase lithium nickel manganese oxide was 100%, and the mass percentage of lithium silicate was 0.58 wt.%. Each vacuum pressure impregnation treatment lasted 5 seconds, with a maximum pressure difference of 40 kPa during each treatment. The interval between two adjacent vacuum pressure impregnation treatments was 5 seconds. Afterward, the cathode sheets were removed and placed in a 60℃ infrared forced-air oven for pre-drying for 5 minutes. Once pre-dried, the cathode sheets were transferred to a vacuum oven and dehydrated at 120℃ for 8 hours. After cooling to room temperature, the precursor material was obtained.

[0076] The vacuum pressure impregnation device used in this embodiment is the same as that in Embodiment 1;

[0077] The precursor material was rolled and slit in an environment with a dew point of -40°C to obtain the composite positive electrode sheet with a size of 30mm×50mm.

[0078] Example 3

[0079] This embodiment provides a method for preparing a composite positive electrode sheet, the method comprising the following steps:

[0080] Unpressed spinel-phase lithium nickel manganese oxide cathode sheets were thoroughly wetted in an anhydrous ethyl acetate solution of n-butyl cyanoacrylate (viscosity 3.7 cP) with a concentration of 3 wt.%. The total mass of spinel-phase lithium nickel manganese oxide was 100%, and the mass percentage of n-butyl cyanoacrylate was 0.8 wt.%. Each vacuum pressure impregnation treatment lasted 4 seconds, the maximum pressure difference during each vacuum pressure impregnation treatment was 30 kPa, and the interval between two adjacent vacuum pressure impregnation treatments was 4 seconds. After that, the cathode sheets were removed and placed in a 60°C infrared forced-air oven for pre-drying for 5 minutes to allow the n-butyl cyanoacrylate to fully polymerize on the surface of the cathode active material and allow the solvent to evaporate. After the cathode sheets were pre-dried, they were transferred to a vacuum oven and dehydrated at 120°C for 8 hours. After cooling to room temperature, the precursor material was obtained.

[0081] The vacuum pressure impregnation device used in this embodiment is the same as that in Embodiment 1;

[0082] The precursor material was rolled and slit in an environment with a dew point of -40°C to obtain the composite positive electrode sheet with a size of 30mm×50mm.

[0083] Example 4

[0084] This embodiment provides a method for preparing a composite positive electrode sheet, the method comprising the following steps:

[0085] LATP solid electrolyte slurry was prepared by mixing LATP nano solid electrolyte particles with an average particle size of less than 200 nm, lithium polyacrylate dispersant, and water in a mass ratio of 12.5:0.5:87, wherein the ratio of the average particle size of the LATP nano solid electrolyte particles to the average particle size of spinel phase lithium nickel manganese oxide was 1 / 25.

[0086] Unpressed spinel-phase lithium nickel manganese oxide cathode sheets were thoroughly wetted in a 10 wt.% LATP solid electrolyte slurry (viscosity 350 cP). The total mass of spinel-phase lithium nickel manganese oxide was 100%, and the mass percentage of LATP solid electrolyte was 3 wt.%. Each vacuum pressure impregnation treatment lasted 5 seconds, the maximum pressure difference during each vacuum pressure impregnation treatment was 50 kPa, and the interval between two adjacent vacuum pressure impregnation treatments was 5 seconds. After that, the cathode sheets were removed and placed in a 60℃ infrared forced-air oven for pre-drying for 5 minutes. After the cathode sheets were pre-dried, they were transferred to a vacuum oven and dehydrated at 120℃ for 8 hours. After cooling to room temperature, the precursor material was obtained.

[0087] The vacuum pressure impregnation device used in this embodiment is the same as that in Embodiment 1;

[0088] The precursor material was rolled and slit in an environment with a dew point of -40°C to obtain the composite positive electrode sheet with a size of 30mm×50mm.

[0089] Example 5

[0090] The difference between this embodiment and Embodiment 1 is that the spinel-phase lithium nickel manganese oxide cathode sheet is replaced with a lithium-rich manganese-based cathode sheet; all other aspects are the same as in Embodiment 1.

[0091] Example 6

[0092] The difference between this embodiment and Embodiment 2 is that the spinel phase lithium nickel manganese oxide cathode sheet is replaced with a lithium-rich manganese-based cathode sheet; all other aspects are the same as in Embodiment 2.

[0093] Example 7

[0094] The difference between this embodiment and embodiment 4 is that the spinel phase lithium nickel manganese oxide cathode sheet is replaced with a lithium-rich manganese-based cathode sheet, while all other aspects are the same as in embodiment 4.

[0095] Example 8

[0096] The difference between this embodiment and Embodiment 1 is that the time for each vacuum pressure impregnation is 30s, the maximum pressure difference during each vacuum pressure impregnation is 80kPa, and the time interval between two adjacent vacuum pressure impregnations is 30s. Everything else is the same as in Embodiment 1.

[0097] Example 9

[0098] The difference between this embodiment and Embodiment 1 is that the time for each vacuum pressure impregnation is 0.5s, the maximum pressure difference during each vacuum pressure impregnation is 10kPa, and the time interval between two adjacent vacuum pressure impregnations is 0.5s. All other aspects are the same as in Embodiment 1.

[0099] Example 10

[0100] The difference between this embodiment and Example 3 is that the viscosity of the anhydrous ethyl acetate solution of n-butyl cyanoacrylate is 1200 cP, while all other aspects are the same as in Example 3.

[0101] Example 11

[0102] The difference between this embodiment and Embodiment 1 is that the porosity of the unpressed spinel phase lithium nickel manganese oxide cathode sheet is 35%, while all other aspects are the same as in Embodiment 1.

[0103] Example 12

[0104] The difference between this embodiment and Embodiment 1 is that the porosity of the unpressed spinel phase lithium nickel manganese oxide cathode sheet is increased to 65% by using p-toluenesulfonyl hydrazine pore-forming agent for pore-forming treatment. All other aspects are the same as in Embodiment 1.

[0105] Comparative Example 1

[0106] This comparative example provides a positive electrode sheet without coating treatment, the preparation method of which includes the following steps:

[0107] Spinel-phase lithium nickel manganese oxide, multi-walled carbon nanotubes, conductive carbon black, and polytetrafluoroethylene were mixed in a mass ratio of 95:1:2:2 and homogenized to prepare a positive electrode slurry. The positive electrode slurry was then coated onto both sides of an aluminum foil current collector and dried to obtain a positive electrode sheet. The areal density of the coating on one side of the positive electrode sheet was 22.30 mg / cm³. 2 The porosity is 48%.

[0108] The positive electrode sheet was placed in a 60℃ infrared forced-air drying oven for 5 minutes to pre-dry. After the positive electrode sheet was pre-dried, it was transferred to a vacuum drying oven and dehydrated at 250℃ for 2 hours. After cooling to room temperature, it was rolled and slit to obtain the positive electrode sheet without coating treatment.

[0109] Comparative Example 2

[0110] This comparative example provides a composite positive electrode sheet, the preparation method of which includes the following steps:

[0111] Spinel-phase lithium nickel manganese oxide cathode active material, lithium borate, and deionized water were heated to 100°C in a pressure-resistant container at a mass ratio of 47:1:18.4 and thoroughly mixed to ensure complete dissolution of lithium borate and deionized water to form a saturated solution. The solution was then rapidly cooled to 20°C to allow the dissolved lithium borate in the liquid phase to precipitate rapidly on the surface of the spinel-phase lithium nickel manganese oxide cathode active material particles, forming a coating layer. After the lithium borate was fully precipitated from the saturated solution, the solution was transferred to a vacuum filtration device to thoroughly filter out the liquid. The solution was then transferred to a tube furnace and dried for 8 hours under a nitrogen protective atmosphere to remove the bound water in the lithium borate coating layer. After cooling to room temperature, the solution was ground and crushed in an environment with a dew point of -40°C and then used in the subsequent cathode homogenization process.

[0112] A positive electrode slurry was prepared by mixing spinel-phase lithium nickel manganese oxide coated with lithium borate, multi-walled carbon nanotubes, conductive carbon black, and polytetrafluoroethylene in a mass ratio of 95:1:2:2 and homogenizing the mixture. The positive electrode slurry was then coated onto both sides of an aluminum foil current collector and dried to obtain a positive electrode sheet. The areal density of the coating on one side of the positive electrode sheet was 22.30 mg / cm³. 2 The porosity is 48%.

[0113] The positive electrode sheet was placed in a 60℃ infrared forced-air drying oven for 5 minutes for pre-drying. After the positive electrode sheet was pre-dried, it was transferred to a vacuum drying oven and dehydrated at 250℃ for 2 hours. After cooling to room temperature, it was rolled and slit to obtain the composite positive electrode sheet.

[0114] Comparative Example 3

[0115] This comparative example provides a composite positive electrode sheet, the preparation method of which includes the following steps:

[0116] Spinel-phase lithium nickel manganese oxide, multi-walled carbon nanotubes, conductive carbon black, and polytetrafluoroethylene were mixed in a mass ratio of 95:1:2:2, and LATP solid electrolyte powder was added. The mixture was homogenized to prepare a positive electrode slurry. The total mass of spinel-phase lithium nickel manganese oxide was 100%, and the mass percentage of LATP solid electrolyte was 3 wt.%. The positive electrode slurry was coated onto both sides of an aluminum foil current collector and dried to obtain a positive electrode sheet. The areal density of the coating on one side of the positive electrode sheet was 21.7 mg / cm². 2 The porosity is 47.5%;

[0117] The positive electrode sheet was placed in a 60℃ infrared forced-air drying oven for 5 minutes for pre-drying. After the positive electrode sheet was pre-dried, it was transferred to a vacuum drying oven and dehydrated at 250℃ for 2 hours. After cooling to room temperature, it was rolled and slit to obtain the composite positive electrode sheet.

[0118] Comparative Example 4

[0119] The difference between this comparative example and Comparative Example 1 is that spinel phase lithium nickel manganese oxide is replaced with an equal amount of lithium-rich manganese-based material; otherwise, they are the same as Comparative Example 1.

[0120] Comparative Example 5

[0121] The difference between this comparative example and Comparative Example 2 is that spinel phase lithium nickel manganese oxide is replaced with an equal amount of lithium-rich manganese-based material; otherwise, they are the same as in Comparative Example 2.

[0122] Test conditions

[0123] The positive electrode sheets provided in Examples 1 to 12 and Comparative Examples 1 to 5 were assembled into lithium-ion batteries for testing. The testing methods are as follows:

[0124] Preparation of the negative electrode sheet: Graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber were mixed with deionized water in a mass ratio of 96:1:1.3:1.7 to prepare a negative electrode slurry. The negative electrode slurry was coated on both sides of a copper foil current collector, dried, and then rolled and die-cut to obtain a negative electrode sheet with dimensions of 33mm × 54mm. The areal density of the coating on one side of the negative electrode sheet was 8.67 mg / cm³. 2 ;

[0125] Preparation of lithium-ion batteries: Composite positive electrode, negative electrode and separator are stacked into a soft pack with a capacity of 1.5Ah; electrolyte is injected, and after formation, subsequent tests are carried out.

[0126] The lithium-ion battery was tested as follows:

[0127] ① High-voltage constant-voltage leakage current test (the cell is charged to 5.0V with constant current and then charged with constant voltage, and the current magnitude and corresponding time when the current reaches stability are monitored; the lithium-rich manganese-based battery is tested at 4.6V).

[0128] ②25℃ DC internal resistance test (test the DC internal resistance of 3C-30s discharge under 10%-50%-90% SOC conditions respectively);

[0129] ③ Cyclic testing at 25℃ / 45℃ showed that the cycle voltage range of the spinel phase nickel manganese oxide-based battery cell was 3.0-4.8V, and the cycle voltage range of the lithium-rich manganese-based battery cell was 2.0-4.6V.

[0130] The test results are shown in Table 1:

[0131] Table 1

[0132]

[0133]

[0134] As can be seen from Table 1, this invention improves the high voltage resistance and electronic conductivity of the positive electrode material by in-situ coating the exposed positive electrode active material surface after the positive electrode slurry has been homogenized and coated and the electrode electronic conductive network has been initially constructed. This improves the fast charging performance and power performance of the secondary battery.

[0135] Comparing Examples 1 and 8-9, it can be seen that the present invention optimizes the impregnation effect by adjusting the parameters of vacuum pressure impregnation, and avoids liquid splashing in the impregnation tank due to excessive pressure difference, which could lead to incomplete immersion of the electrode sheet, or excessive pressure difference that could affect the impregnation effect. In Example 8, due to liquid splashing, the electrode sheet was not fully immersed, and repeated impregnation and coating were not possible, resulting in increased side reactions between the positive electrode and the electrolyte, thus increasing the leakage current of the assembled battery. In Example 9, due to the small pressure difference of vacuum pressure impregnation, the coating additive could not fully penetrate into the interior of the positive electrode sheet, resulting in insufficient coating and failure to repeat impregnation and coating, which increased the side reactions between the positive electrode and the electrolyte, thus increasing the leakage current of the assembled battery.

[0136] Comparing Example 1 and Example 10, it can be seen that the present invention controls the viscosity of the fluid containing the coating additive, avoiding the use of a fluid containing the coating additive with a high viscosity, which would cause the coating agent to not fully penetrate to the bottom of the positive electrode.

[0137] Comparing Examples 1 and 11-12, it can be seen that the present invention, by controlling the porosity of the unpressed spinel-phase lithium nickel manganese oxide cathode sheet, enables the cathode sheet to be fully wetted, thereby improving the electronic conductivity of the cathode sheet and ensuring the smooth progress of the coating process. In Example 11, the unpressed spinel-phase lithium nickel manganese oxide cathode sheet has a lower porosity, resulting in a poorer coating effect compared to Example 1, and thus the overall performance of the assembled battery is worse. In Example 12, the unpressed spinel-phase lithium nickel manganese oxide cathode sheet has larger pores, leading to insufficient initial conductive electronic network connections. This results in a higher content of coating additives after coating, a thicker coating layer, increased internal resistance of the battery, and decreased cycle performance due to the reduced kinetic performance of the cathode sheet.

[0138] Comparing Example 1 and Comparative Examples 1-2, it can be seen that if the positive electrode active material is not coated, there are more side reactions between the positive electrode material and the electrolyte, thus reducing the stability of battery cycling. The existing technology uses a pre-coating treatment of the positive electrode active material before preparing the positive electrode slurry. Since the coating layer covers the electron transport sites on the surface of the positive electrode active material, it further reduces the electronic conductivity of the positive electrode material, resulting in an increase in DC resistance.

[0139] Comparing Example 4 with Comparative Example 3, it is shown that the technical solution of directly adding coating material to the positive electrode slurry for mixing and slurry preparation has the disadvantage that some conductive agents are not covered and are exposed to the positive electrode surface and come into contact with the electrolyte, which leads to an increase in side reactions, resulting in an increase in battery leakage current and a decrease in cycle performance. Therefore, it cannot achieve all the technical effects of the present invention.

[0140] The applicant declares that the present invention is illustrated by the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite positive electrode sheet, characterized in that: The method comprises the following steps: Immersing an unpressed positive electrode sheet in a fluid containing a coating additive, and obtaining a precursor material after drying, wherein the positive electrode sheet does not contain the coating additive; The precursor material is pressed to obtain the composite positive electrode sheet.

2. The method according to claim 1, characterized in that The material of the positive electrode sheet includes a positive electrode active material, a conductive agent and a binder in a mass ratio of (92-97):(1-3):(2-5); Preferably, the charging voltage platform of the positive electrode active material is not less than 4.4V; Preferably, the conductive agent is interspersed between the positive electrode active materials to form an electronic conductive network; Preferably, the conductive agent material comprises a one-dimensional conductive agent material; Preferably, the one-dimensional conductive agent material comprises at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes or vapor-grown carbon fiber reinforcements; Preferably, based on the total mass of the material of the positive electrode sheet being 100%, the mass percentage of the one-dimensional conductive agent material is 0.1wt.%-2wt.%; Preferably, the porosity of the positive electrode sheet is 45%-55%.

3. The method according to claim 1 or 2, characterized in that: The impregnation process includes using a vacuum pressure impregnation device to perform vacuum pressure impregnation treatment; Preferably, the vacuum pressure impregnation device comprises an impregnation unit, a vacuum unit and a pressurizing unit; Preferably, the upper portion of the impregnation unit is connected to the vacuum unit via a first connecting valve; Preferably, the vacuum unit comprises a vacuum tank and a vacuum pump, the vacuum tank is connected to the impregnation unit through a first connecting valve, and the vacuum unit is used to extract gas in the impregnation unit to form a vacuum; Preferably, the upper portion of the impregnation unit is connected to the pressurizing unit via a second connecting valve; Preferably, the pressurizing unit comprises a pressure tank and a pressure pump, the pressure tank is connected to the impregnation unit through a second connecting valve, and the pressurizing unit is used to generate pressure to immerse the coating additive into the unpressed positive electrode sheet of the impregnation unit; Preferably, the impregnation unit comprises an impregnation tank, an infrared drying oven and a conveying unit, wherein the conveying unit conveys the unpressed positive electrode sheet to the impregnation tank for impregnation treatment, and after the impregnation treatment, conveys it to the infrared drying oven for drying to obtain a precursor material; Preferably, the duration of each vacuum pressure impregnation treatment is 1-20 s, preferably 2-5 s; Preferably, the maximum difference in pressure during each vacuum pressure impregnation treatment is 20-60 kPa, preferably 30-50 kPa; Preferably, the interval between two adjacent vacuum pressure impregnation treatments is 1-20 seconds, preferably 2-5 seconds.

4. The method according to claim 2, characterized in that: The coating additive includes a lithium ion conductor; Preferably, the lithium ion conductor comprises any one or a combination of at least two of lithium borate, lithium silicate, lithium aluminate, lithium phosphate, polycyanoacrylate or an inorganic solid electrolyte; Preferably, based on the total mass of the positive electrode active material being 100%, the mass percentage of the coating additive is 0.5wt.%-5wt.%, preferably 0.5wt.%-3wt.%.

5. The method according to claim 4, characterized in that When the coating additive is lithium borate, based on the total mass of the positive electrode active material being 100%, the mass percentage of the lithium borate is 0.5 wt.%-2 wt.%.

6. The method according to claim 4, characterized in that When the coating additive is an inorganic solid electrolyte, the average particle size of the inorganic solid electrolyte is ≤200 nm, and the ratio of the average particle size of the inorganic solid electrolyte to the average particle size of the positive electrode active material is ≤1 / 20, preferably 1 / 30-1 / 20; Preferably, when the coating additive is an inorganic solid electrolyte, the fluid containing the coating additive further includes a dispersant; Preferably, based on 100% of the total mass of the positive electrode active material, the mass percentage of the dispersant is not higher than 1 wt.%.

7. The method according to any one of claims 1 to 6, characterized in that The solvent in the fluid containing the coating additive includes at least one of deionized water, ethanol, acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide; Preferably, the concentration of the solute in the fluid containing the coating additive is 1wt.%-15wt.%, preferably 2wt.%-8wt.%; Preferably, the viscosity of the fluid containing the coating additive is not higher than 1000 cP, preferably not higher than 500 cP.

8. A composite positive electrode sheet, characterized in that: The composite positive electrode sheet is prepared by the method for preparing a composite positive electrode sheet according to any one of claims 1 to 7.

9. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the positive electrode sheet comprises the composite positive electrode sheet according to claim 8.

10. The secondary battery according to claim 9, characterized in that: The negative electrode active material in the negative electrode sheet includes at least one of graphite, soft carbon, hard carbon, silicon oxide, silicon carbon or lithium titanate; Preferably, the electrolyte comprises a metal salt, an additive and a solvent; Preferably, the metal salt comprises a lithium salt; Preferably, the lithium salt comprises at least one of lithium hexafluorophosphate, lithium bis(trifluoromethyl)sulfonyl imide or lithium bis(trifluoromethyl)sulfonyl imide; Preferably, the additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, propylene sulfate, 1,3-propane sultone, 1,4-butane sultone, dimethyl methanedisulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium difluorooxalatophosphate or lithium dioxalatoborate; Preferably, the solvent comprises any two or a combination of at least three of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, propyl propionate, ethyl propionate, methyl propionate, fluoroethylene carbonate or fluoroethyl acetate.